Proteomics of isolated sieve tubes from Nicotiana tabacum: sieve element–specific proteins reveal differentiation of the endomembrane system - Liu, Yan; Vasina, Viktoriya V.; Kraner, Max; Peters, Winfried S.; Sonnewald, Uwe; Knoblauch, Michael (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Symplasmicly connected cells called sieve elements form a network of tubes in the phloem of vascular plants. Sieve elements have essential functions as they provide routes for photoassimilate distribution, the exchange of developmental signals, and the coordination of defense responses. Nonetheless, they are the least understood main type of plant cells. They are extremely sensitive, possess a reduced endomembrane system without Golgi apparatus, and lack nuclei and translation machineries, so that transcriptomics and similar techniques cannot be applied. Moreover, the analysis of phloem exudates as a proxy for sieve element composition is marred by methodological problems. We developed a simple protocol for the isolation of sieve elements from leaves and stems of Nicotiana tabacum at sufficient amounts for large-scale proteome analysis. By quantifying the enrichment of individual proteins in purified sieve element relative to bulk phloem preparations, proteins of increased likelyhood to function specifically in sieve elements were identified. To evaluate the validity of this approach, yellow fluorescent protein constructs of genes encoding three of the candidate proteins were expressed in plants. Tagged proteins occurred exclusively in sieve elements. Two of them, a putative cytochrome b561/ferric reductase and a reticulon-like protein, appeared restricted to segments of the endoplasmic reticulum (ER) that were inaccessible to green fluorescent protein dissolved in the ER lumen, suggesting a previously unknown differentiation of the endomembrane system in sieve elements. Evidently, our list of promising candidate proteins (SI Appendix, Table S1) provides a valuable exploratory tool for sieve element biology.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Phloem; Proteomics; Sieve element; Sieve tube endomembrane system